Fifty years of 60 Minutes [large type] : the inside story of television's most influential news broadcast - Fager, Jeffrey (Thorndike Press, a part of Gale, a Cengage Company, 2017)
The executive producer of 60 Minutes tells the inside story of the legendary program, from its almost accidental birth through five decades of in-depth reporting by talented producers and beloved correspondents, including Harry Reasoner, Mike Wallace, Morley Safer, Ed Bradley, Lesley Stahl, Steve Kroft and others.